Оптимізація базально-болюсної інсулінотерапії цукрового діабету 2-го типу на підставі фармакоекономічного аналізу - Колбін, А. С. (Clinical Endocrinology and Endocrine Surgery, 2010)
Pharmacoeconomic analysis of the use of insulin analogues for the treatment of patients with diabetes mellitus type 2 was conducted for substantiation of rationalization the allocation of public funds to improve the quality of medical care. It is shown that the most economical is the use of insulin glargine as monotherapy or combination with insulin glulisine for the treatment of patients with diabetes type 2 for whom the insulin therapy is recommended.